UPDATING THE HIGHER EDUCATION CURRICULUM IN EDUCATION AND INFORMATICS STUDY PROGRAMS IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Rima Yustika (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
This research examines the study of updating the Higher Education curriculum in education and informatics study programs in the era of the industrial revolution 4.0. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. The results of this study indicate that higher education is not just a place where students gain knowledge and skills but also a provision for students to complete the industrial era. Based on the study, it was found that students of the Education and informatics study program had good job readiness in facing the world of work in the 4th industrial era, both in the moral aspects and the code of ethics in the teaching aspects and aspects of human values. This transformation occurred and directly affected the performance of the lecturers of the education and informatics study program as a result of the Industrial Revolution 4.0 to continue to develop in various ways, especially in the field of technology, namely digitalization. Not only that, the government's demand to produce a generation that is ready for the times and the industrial revolution that is happening makes the government have to prepare various policies, especially updating the curriculum so that it is in line and in line with the demands of the world in the industrial revolution 4.0 that is happening.